BOARD OF COMMISSIONERS’ MODERATING EFFECT ON RISK AND INTELLECTUAL CAPITAL DISCLOSURES TOWARD FIRM VALUE: EMPIRICAL EVIDENCE FROM INDONESIA’S FINANCIAL SECTOR - Dedi Ardianto; Holiawati; Nofryanti (ZILLZELL MEDIA PRIMA, 2025)
This study investigates the effect of Enterprise Risk Management Disclosure (ERMD) and Green Intellectual Capital Disclosure (GICD) on firm value, with the moderating role of the Board of Commissioners, in financial sector companies listed on the Indonesia Stock Exchange from 2019 to 2023. Using panel data regression analysis on 185 firm-year observations, the study reveals that ERMD has a significant negative effect on firm value, indicating that such disclosures may be perceived as mere compliance rather than value-enhancing strategies. Meanwhile, GICD shows no significant impact on firm value, suggesting that environmental-related intangible assets are not yet fully recognized by investors. Furthermore, the Board of Commissioners does not moderate the relationship between either ERMD or GICD and firm value, highlighting limited oversight effectiveness in these areas. The findings imply that non-financial disclosures and corporate governance mechanisms in the financial sector have not been fully leveraged to enhance firm performance. This study contributes to the literature on corporate governance and sustainability disclosure in emerging markets.